Inquiry of the discomfort offered for different tatamis used in the practical of the judo - Sebastião Iberes Lopes Melo; Carlos Rodrigo de Melo Roesler; Saray Giovana dos Santos (Universidade Federal de Santa Catarina, 2007)
Este estudo, caracterizado de duas formas, exploratório e diagnóstico, com o objetivo de investigar o conforto fornecido por diferentes tatames utilizados na prática do judô. Na pesquisa exploratória, dois atletas executaram projeções (Ippon-Seoi-Nage) e quedas da conseqüente (Zempô-Kaiten-Ukemi) para cada segmento do corpo avaliado (pulso e quadril), em sete tipos de tatame (seis sintéticos e uma de palha). Um acelerômetro triaxial foi fixado no atleta que era projetado (primeiramente no punho e depois no quadril), para as medidas respectivas do impacto. Para a pesquisa de campo, 63 judocas, executando as mesmas técnicas, responderam um protocolo sobre a percepção do desconforto sobre cada tipo de material. Os dados foram coletados por meio do programa SAD32 e as curvas experimentais do acelerômetro foram importadas para o software de MATLAB (versão 5, 1999), para parametrização e derivação a fi m obter o a, q e jerk, respectivamente. Os resultados obtidos para a percepção subjetiva e na parametrização das curvas (a and q), classificaram os tatames quanto ao desconforto, sendo esta classifi cação na ordem crescente para o segmento do punho: A, B, F, G, D, C, E; e para o quadril: A, F, B, C, G, D, E. Acredita-se que os procedimentos descritos aqui para a realização do a, q e os índices do jerk serão úteis para a classifi cação do desconforto fornecido por outros materiais submetidos ao impacto tal como sobresolas e solas de sapatas esportivo. ABSTRACT This study, characterized both as field and investigative had the objective of investigating the comfort provided by different tatamis for the fall absorption practice (ukemi). In the investigative research performed at laboratory, seven types of tatamis were tested (six synthetic and one straw made) in which 2 athletes performed projections (Ippon-Seoi- Nage) and consequent falls (Zempô-Kaiten-Ukemi) for each body segment evaluated (wrist and hip). A triaxial accelerometer was fastened to the athlete, first at the wrist and then at the hip, for the respective impact measures. For the field research, 63 judo fi ghters, performing the same fall projection, who inferred in a protocol the discomfort perception about each type of material, tested the same tatamis. The data were collected through the SAD 32 program and the experimental acceleration curves were imported for the MATLAB (version 5, 1999) software, which were parameterized and derived in order to obtain the a, q and jerk calculations, respectively. The results obtained for both the subjective perception, in the parameterization of curves (a and q) and for the values of jerk, ended up by classifying the tatamis with regard to the discomfort characteristic, being this classifi cation in crescent order for the wrist segment: A, B, F, G, D, C, E; and for the hip: A, F, B, C, G, D, E. It is believed that the procedures here described for the attainment of the a, q and jerk indexes will be useful for the classifi cation of discomfort provided by other materials submitted to impact such as insoles and soles of sportive shoes.